New approach for the molecular beam epitaxy growth of scalable WSe2 monolayers. (8th April 2020) - Vergnaud, Céline; Dau, Minh-Tuan; Grévin, Benjamin; Licitra, Christophe; Marty, Alain; Okuno, Hanako; Jamet, Matthieu
Abstract: The search for high-quality transition metal dichalcogenides mono- and multi-layers grown on large areas is still a very active field of investigation. Here, we use molecular beam epitaxy to grow WSe2 on 15 × 15 mm large mica in the van der Waals regime. By screening one-step growth conditions, we find that very high temperature (>900 °C) and very low deposition rate (<0.15 Å min −1 ) are necessary to obtain high quality WSe2 films. The domain size can be as large as 1 µ m and the in-plane rotational misorientation of 1.25°. The WSe2 monolayer is also robust against air exposure, can be easily transferred over 1 cm 2 on SiN/SiO2 and exhibits strong photoluminescence signal. Moreover, by combining grazing incidence x-ray diffraction and transmission electron microscopy, we could detect the presence of few misoriented grains. A two-dimensional model based on atomic coincidences between the WSe2 and mica crystals allows us to explain the formation of these misoriented grains and gives insight to achieve highly crystalline WSe2 .